Commiphorines A and B, unprecedented sesquiterpenoid dimers from Resina Commiphora with striking activities on anti-inflammation and lipogenesis inhibition. Issue 23 (24th October 2019) - Dong, Lu; Qin, Da-Peng; Di, Qian-Qian; Liu, Ying; Chen, Wei-Lin; Wang, Shu-Mei; Cheng, Yong-Xian
Abstract : Commiphorines A (1 ) and B (2 ), two dimeric sesquiterpenoids featuring unusual polycyclic systems, and two intermediates 3 and 4, were isolated from Resina Commiphora . Abstract : Commiphorines A (1 ), an unprecedented sesquiterpenoid heterodimer featuring a 5/7(5)/4/10/5 ring system, and B (2 ), a dimeric sesquiterpenoid possessing an unusual 1, 4-dioxin motif and a 6/6/5/6/6/6 polycyclic system, and two intermediates 3 and 4 were isolated from Resina Commiphora . A plausible biosynthetic route for 1 and 2 was proposed. Compound 2 could significantly suppress LPS-induced inflammation through NF-κB and MAPK signaling pathways in mouse peritoneal macrophages. Compounds 1 and 2 could inhibit lipid synthesis in HepG2 cells.